2016
DOI: 10.13063/2327-9214.1266
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Prevalence, Treatment, and Control Of Metabolic Conditions In New York City Adults Using 2013 Primary Care Electronic Health Records: A Surveillance Validation Study

Abstract: Introduction:Electronic health records (EHRs) can potentially extend chronic disease surveillance, but few EHR-based initiatives tracking population-based metrics have been validated for accuracy. We designed a new EHR-based population health surveillance system for New York City (NYC) known as NYC Macroscope. This report is the third in a 3-part series describing the development and validation of that system. The first report describes governance and technical infrastructure underlying the NYC Macroscope. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…19,20 In brief, NYC Macroscope indicators for diabetes, hypertension, smoking, and obesity prevalence performed well according to a priori criteria for agreement (Table 2), and each of these demonstrated high sensitivity and specificity (0.89-1.00) in the chart review study of records from providers contributing to the NYC Macroscope. Although hyperlipidemia prevalence met many of the a priori criteria, sensitivity and specificity were not as good (0.72 and 0.58, respectively).…”
Section: Nyc Macroscope Validation Resultsmentioning
confidence: 99%
“…19,20 In brief, NYC Macroscope indicators for diabetes, hypertension, smoking, and obesity prevalence performed well according to a priori criteria for agreement (Table 2), and each of these demonstrated high sensitivity and specificity (0.89-1.00) in the chart review study of records from providers contributing to the NYC Macroscope. Although hyperlipidemia prevalence met many of the a priori criteria, sensitivity and specificity were not as good (0.72 and 0.58, respectively).…”
Section: Nyc Macroscope Validation Resultsmentioning
confidence: 99%
“…Some researchers and communities have begun work to validate these EHR estimates through neighborhood-level surveys to better assess accuracy of EHR-based estimates. 38 , 41 This process of validation will be important to allay concerns about selection bias for those accessing and represented in an EHR-based estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic Health Records (EHR) has been increasingly used as a tool for public health surveillance by local and national jurisdictions [1]. For example, recent studies in New York City (NYC) reported that the prevalence estimates from NYC Macroscope, an EHR-based surveillance system in NYC [2], were comparable to the survey-based estimates for diabetes, hypertension, and smoking [3,4]. EHR often cover more people (n ≥ 100, 000) than traditional population health surveys and, and once the infrastructure is in place, the data collection occurs in near real-time without additional recruitment or interviewing cost.…”
Section: Introductionmentioning
confidence: 99%
“…It comprises measurement error (e.g., due to the use of non-standardized instruments across sites), extraction error, or the collection of proxy-measurement (e.g., due to the recording without distinction of both self-report and actual measurements). McVeigh et al [3] reported such subjectlevel discrepancies by examining a chart review of participants who both visited NYC Macroscope providers and also participated in the NYC Health and Nutrition Examination Survey (HANES), a population-representative survey with field interviews and biospecimen collection. Assuming NYC HANES measurements as "gold-standard, " the chart review found a 5% subject-level error for obesity, 19% for depression, and 19% for influenza vaccination.…”
Section: Introductionmentioning
confidence: 99%